Characteristic of Fishball from Mixed-Surimi of Decapterus spp. and Lutjanus sp. on Chilling Storage - . Chairita; Linawati Hardjito; Joko Santoso; . Santoso (Jurnal Pengolahan Hasil Perikanan Indonesia, 2009)
The utilization of scad (Decapterus spp.) has not been done optimally. This species is a potential fish to be processed into surimi that is a raw material of fish jelly products, such as fishball. It contains red meat in greater proportion compared to white meat. For this reason, surimi of scad (Decapterus spp.) was produced using alkaline leaching method and mixed with red snapper (Lutjanus sp) surimi to be used a raw material of fishball. The fishball was added by chitosan at concentration of 0.1% as preservative, while carrageenan was added at concentration of 1% as gelling agent. The fishball was stored in chilling condition (0-4 oC). The results indicated that surimi of Decapterus spp. being leached twice showed the same quality as white meat surimi. Fishball containing red snapper surimi and scad surimi of 1:3 added by 25% of tapioca starch showed good physical and sensory characteristics. The mixed surimi of fresh fish meat was better in term of its physical, chemical, and sensory characteristics compared to the frozen one. Chitosan added at 0.1% could preserve the fishball for two weeks on chilling storage (0-4 oC) without causing any change of its physical and chemical characteristics. The fishball produced has a better flavor and texture was similar to commercial one.Keywords: chilling storage, Decapterus spp, fishball, Lutjanus sp, mixed-surimi.